Penggunaan Metode Make A Macth Untuk Meningkatkan Hasil Belajar PAI Kelas IV SDN 04 Manggilang - Nurjannah Nurjannah; Zulfani Sesmiarni; Rodi Rodi; Meyriza Hamda; Desri Wahyuni; Yona Widya Eka Putri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the low learning outcomes of students in the subject matter of Emulating Asmaul Husna in grade IV children at SDN 04 Manggilang. One solution to this problem is to implement activities using the Make a match method, this study aims to improve the learning outcomes of children in Grade IV SDN 04 Manggilang. The method used in this study is the Classroom Action Research (CAR) method. This classroom action research was carried out in 2 cycles, each cycle had 2 meetings. The data collection techniques used were observation and documentation. The results of this study show an increase in children's grades from pre- action, cycle I and cycle II which can be clearly described as follows: BB grades in pre-action were 10 children or 70%, then in cycle 1 it became 6 children or 40%, then in cycle II it became 1 child or 10%. Based on the results of the study above, the researcher suggests that teachers use the Make a Match method as an alternative activity in improving children's learning outcomes.